Evaluation of drinking water quality index (DWQI) and its seasonal variations in hard rock aquifers of Madurai district, Tamilnadu - Thivya, C.; Chidambaram, S.; Thilagavathi, R.; Nepolian, M.; V.S, Adithya (International Journal of Advanced Geosciences, 2014)
Groundwater is an important source of water supply throughout the world. The quantity and the suitability of groundwater for human consumption are determined by its physical, chemical and bacteriological properties. There are several difficulties for the accessibility of groundwater resources in hard rock areas as wide and erratic variation of essential parameters (i.e., fractures, joints, and porosity) characterizes the groundwater system. Madurai district is such one among them with hard rock regions. A study was carried out in this district of Tamil Nadu for four seasons (Pre-Monsoon, Southwest monsoon, North east monsoon and Post-monsoon), India to assess the drinking water quality and their seasonal variations through DWQI (Drinking water quality index). In order to obtain a synoptic view of quality of groundwater for drinking purpose, a total of 216 groundwater samples for four seasons are collected representing the entire district. pH, temperature, TDS and conductivity of the water samples were measured in the field using a portable water-analysis kit. Sampling and analysis was carried out using standard procedures.The physicochemical parameters considered for the Drinking water quality index (DWQI) include pH, TDS, cations such as Ca2+, Mg2+, Na+ and K+, anions such as Cl?, SO42?, HCO3?, F? and NO3?, Heavy metals like U, Zn, Cd, pb and Cu were also considered for DWQI. The poor water quality may be due to the presence of excess amounts of TDS, Na+, HCO3?, and Cl? in the study area. The spatial distribution of DWQI indicates that poor quality of drinking water is observed in patches in different regions and it varies according to the seasons. The change in DWQI in the region implies the seasonal variations of monsoon may be due to leaching of ions, weathering and ion exchange processes. Keywords:Drinking Water Quality Index, Weathering, Leaching, Geochemistry.